Fundamental liberties under the Federal Constitution : a critical analysis - Shuaib, Farid Sufian (Sweet & Maxwell Asia, 2012)
Fundamental liberties under the Malaysian Federal Constitution which came into being in year 1957 shares similarities with human rights contain in the international instruments. One might even say that the constitutional rights are influenced by an earlier international document namely the Universal Declaration of Human Rights 1948. The construction of the fundamental liberties however is very much confined within the four walls of the constitutional documents. The courts have taken great pains to emphasise that although international instruments and cases from other jurisdiction may be referred to, at the end the Malaysian constitution should be construed according to its own language.